Analysis of Language Styles in Fiersa Besari's Songs Based on Hermeneutic Study - Heni, Heni Subagiharti; Syahfitri Handayani, Diah; Herawati, Tuti (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
The purpose of this study was to determine the style of language and describe the meaning of songs by Fiersa Besari through a Hermeneutical approach based on the theory of Friedrich Ernst Daniel Schleirmacher with the theory of Grammatical Interpretation and Psychological Interpretation. This type of research method is descriptive qualitative. Data collection methods and techniques used in this study, namely library methods and field methods where the techniques used, namely recording techniques, observing techniques and note-taking techniques. The data analysis technique focuses on the workings of hermeneutics in discussing the interpretation of meaning. The results of this study the authors conclude that the lyrics of the song Fiersa Besari use a lot of figurative language such as metonymy, hyperbole, pleonasm, personification, metaphor, sarcasm, eroticism, assonation, polisyndenton, epithet, satire, cynicism, and irony. The meanings contained in the lyrics of the song are: (1) about a long-distance love story, (2) a devotional song to improve attitudes towards the Indonesian homeland, (3) a story of unrequited love, (4) satire to the people and the government of Indonesia.